Implikasi Penguasaan Tatabahasa Arab Terhadap Kemahiran Menulis dalam Kalangan Pelajar Asasi Universiti Awam Malaysia: The Implications of Arabic Grammar Mastery on Writing Skills among Foundation Students in Malaysian Public Universities - Wan Mokhtar, Wan Rohani; Abd. Rahman, Mohd Zaki; Mohamed Adnan, Mohamad Azrien; Mohd Salleh, Nor Hazrul (Al-Basirah Journal, 2020)
Arabic language learning in Malaysia serves not only as a language of knowledge but also as a means of communication. Emphasis on grammar in the teaching and learning of Arabic is essential, as grammar is one of the key factors influencing the mastery of language skills. The purpose of this study is to identify the level of Arabic grammar mastery among foundation-level students in Malaysian public universities, to analyse their writing proficiency in terms of grammatical accuracy, and to determine the implications of grammar mastery on writing skills. This study adopts a quantitative approach, with research instruments consisting of an Arabic grammar proficiency test and a writing skills assessment. The respondents in this study comprise students who have completed the Malaysian Certificate of Education (SPM) and have proceeded to foundation-level studies in Malaysian public universities. Descriptive analysis is employed to determine the students’ level of mastery. Writing errors are identified based on deviations from the rules of standard Arabic grammar. The implications of Arabic grammar mastery on writing skills are assessed based on the respondents’ performance in the tested topics and their ability to apply them in essay writing. The findings indicate that mastery of Arabic grammar has a significant impact on writing skills.